Janus effect of FeCo dual atom catalyst with Co as active center in acidic oxygen reduction reaction - Long-Ji Yuan; Zhen-Yu Miao; Xu-Lei Sui; Chi-Feng Lee; Qi Li; Mei-Jie Yin; Li-Xiao Shen; Ying-Rui Lu; Zi-Gang Zhao; Yu-Zhe Liu; Lin-Sheng Zhu; Wei Gong; et al. (Nature Communications)
Abstract Dual-atom catalysts (DACs) represent a frontier in heterogeneous electrocatalysis for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells. However, the dynamic evolution of active-site structure complicates mechanistic understanding. Herein, alloyed Fe-Co DACs with strong Fe-Co bonds are synthesized via molecular chelation and ionic coupling strategies. In-situ spectroscopy combined with theoretical calculation reveals the Janus effect of Fe-Co dual-atom sites: Co serves as the primary catalytic center for the 4e- process with Fe as the cooperative sites to absorb the *OH. This division-of-labor mechanism lowers the theoretical overpotential from 1.14 V to 0.43 V for acidic oxygen reduction reaction. Thus, the catalyst achieves a 0.852 V half-wave potential and 1.14 W cm−2 power density (2.0 bar H₂-O₂), sustaining 81% peak power after 10,000 cycles. These findings clarify DAC configuration-mechanism relationships, guiding the design of high-performance DACs.